2017
DOI: 10.1155/2017/7516409
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Optimization of Natural Dye from Hambo Hambo(Cassia singueana)Plant Used for Coloration of Tanned Leather Materials

Abstract: This investigation was aimed at introducing natural dye extracted from the bark of Cassia Singueana plant for dyeing chrome tanned sheep skin crust leather. The colorant was extracted by aqueous extraction and its strength evaluated using UV-Visible spectroscopy. The extraction with the highest strength (3.9 at max of 400 nm) was obtained at temperature of 95 ∘ C, concentration of 60 g/l, and time of 60 minutes. The possibility of using aloe vera juice and mango bark extract as natural mordants for leather col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Natural dye was extracted from Cassia singueana plant was successfully used in dyeing of silk fabric in the presence of Aloe Vera juice as natural mordant [8]. Tanned leather materials were dyed using extracted natural dye from this plant in the presence of natural mordants extracted from Aloe Vera and mango bark [9]. The possibility of using extract of bark of mango tree (Mangifera indica) as a mordant to dye cotton fabric with natural dye (bitter leaves) has been investigated by Wangatia [10].…”
Section: Introductionmentioning
confidence: 99%
“…Natural dye was extracted from Cassia singueana plant was successfully used in dyeing of silk fabric in the presence of Aloe Vera juice as natural mordant [8]. Tanned leather materials were dyed using extracted natural dye from this plant in the presence of natural mordants extracted from Aloe Vera and mango bark [9]. The possibility of using extract of bark of mango tree (Mangifera indica) as a mordant to dye cotton fabric with natural dye (bitter leaves) has been investigated by Wangatia [10].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of 4/5 on dry basis implies that leather has good to very good fastness, while the rate of 5 showed very good fastness on the finished leather (Çolak and Ortafidan, 2016;Berhanu & Ratnapandian, 2017). It was observed that the higher parts of gambir in the finishing process did not increase the wet and dry rubbing fastness.…”
Section: Rub Fastnessmentioning
confidence: 97%
“…The high temperature degrades and unstabilize the desired polyphenol compounds. Opposite to this the low temperature slows downs the color extraction (Berhanu & Ratnapandian, 2017;Khoo et al, 2017). This material also occupies the space and hold high amount of water so, the solvent ratio is kept from 1:100 to 1:200.…”
Section: D Surface Plots Depicting the Interaction Between Experimental Variables And Response Dye Yieldmentioning
confidence: 99%